N6-Methyladenosine, DNA Repair, and Genome Stability - Qu, Fei; Tsegay, Pawlos S.; Liu, Yuan (Frontiers in Molecular Biosciences, 2021)
N6-methyladenosine (m6A) modification in mRNAs and non-coding RNAs is a newly identified epitranscriptomic mark. It provides a fine-tuning of gene expression to serve as a cellular response to endogenous and exogenous stimuli. m6A is involved in regulating genes in multiple cellular pathways and functions, including circadian rhythm, cell renewal, differentiation, neurogenesis, immunity, among others. Disruption of m6A regulation is associated with cancer, obesity, and immune diseases. Recent studies have shown that m6A can be induced by oxidative stress and DNA damage to regulate DNA repair. Also, deficiency of the m6A eraser, fat mass obesity-associated protein (FTO) can increase cellular sensitivity to genotoxicants. These findings shed light on the novel roles of m6A in modulating DNA repair and genome integrity and stability through responding to DNA damage. In this mini-review, we discuss recent progress in the understanding of a unique role of m6As in mRNAs, lncRNAs, and microRNAs in DNA damage response and regulation of DNA repair and genome integrity and instability.